The influence of marine service charges and port tariffs on container port competitiveness to shipping lines in Southern Africa - Du Toit, Fryhoff Albertyn (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEng)--Stellenbosch University, 2025.